Determining job category using AWS machine learning cloud services (Моделювання, керування та інформаційні технології, 2023)
In this article, the focus is on the modern role of information technology in the labor market, with special emphasis on automation and optimization of processes through cloud solutions. The main theme is the creation of a system for the automatic categorization of job vacancies using Amazon Web Services (AWS). The authors describe the key advantages of implementing cloud technologies, such as scalability, cost savings, availability, and high productivity. Specific AWS services are then discussed, including ECS, DynamoDB, AWS Glue, Amazon SageMaker, and AWS Lambda, which can be applied for the implementation of this system. The article aims to show how AWS technologies can be used to improve efficiency.